Subchronic Toxicity Study of Oral Anthrafuran on Rabbits - Michael I. Treshchalin; Helen M. Treshalina; Vasilisa A. Golibrodo; Andrey E. Shchekotikhin; Eleonora R. Pereverzeva (MDPI AG, 2021)
A new antitumor multi-target drug anthrafuran, with cellular targets such as topoisomerase I/II and some protein kinases, was obtained in Gause Institute of New Antibiotics and was demonstrated to have a reliable specific effect on different murine and human tumor models by oral administration. In this study, we focused on the evaluation of subchronic toxicity of oral anthrafuran drug formulation (AF) on Chinchilla rabbits. The absence of any changes in the condition or behavior of animals was shown for oral anthrafuran. Changes with reversible and dose-dependent hepato- and nephrotoxicity at low doses, as well as hemato- and gastrointestinal toxicity at high doses, were confirmed pathomorphologically. The identified toxic properties are extremely valuable, since oral anthrafuran does not have the limiting cardio- and myelotoxicity. Anthrafuran with 2 mg/kg/day or 6 mg/kg/day doses was administrated orally over 15 days. Investigations include assessment of the body weight, hematological and serum biochemical parameters and urinalysis, electrocardiography and pathomorphological evaluation of the internal organs. Quantitative data were processed statistically with Student's t-Test, p < 0.05. Revealed during the subchronic study were the favorable toxicological properties of oral anthrafuran as opposed to clinical anthracyclines, oral idarubicin, or parenteral doxorubicin, which allows it to be considered promising for further research.